Insights from a Decade of Optimizing Emergency Medical Services Across Three Major Regions in Switzerland - Christoph Strauss; Michael Schmid; Daniel Kliem; Martin Müller (Emergency Care and Medicine)
Prehospital care, and especially emergency medical services (EMSs), are facing an increasing demand, while experiencing financial pressure. Strategies aimed at improving prehospital care management emphasize the efficient utilization of resources, but often overlook the long-term implications for the prehospital healthcare system, encompassing emergency medical services, emergency departments, and healthcare authorities. This paper draws on almost ten years of improvement in EMS’ key performance indicators such as response time or overtime in Switzerland, using Discrete Event Simulation. Three representative simulation studies are used to reflect on the optimization potential of alternative bases and rosters, methodological limitations, and the uptake of the derived recommendations. The results demonstrate that EMSs’ efficiency gains in resource utilization increasingly come into conflict with emergency departments’ and healthcare authorities’ policies, indicating a need to enrich Discrete Event Simulation with a systemic perspective. A new methodology that conceptualizes long-term prehospital care planning as an interdisciplinary and iterative process utilizing a novel combination of System Dynamics and Discrete Event Simulation is proposed.